Women's views and knowledge regarding healthcare seeking for gestational diabetes in the postpartum period: A systematic review of qualitative/survey studies. Issue 2 (November 2015) - Van Ryswyk, Emer; Middleton, Philippa; Shute, Elen; Hague, William; Crowther, Caroline
Highlights: Counselling relating to the emotional impact of a GDM diagnosis is important. Improved education on type 2 diabetes risk reduction is needed for women with GDM. A more pro-active approach to postpartum care for GDM is preferable to women. Abstract: Aim: To identify factors influencing postpartum healthcare seeking, from the perspective of women who have experienced gestational diabetes mellitus (GDM). Methods: Systematic review that searched PubMed, Web of Science, EMBASE and CINAHL on 27th February 2013. Qualitative studies and surveys, with women as participants, which reported pre-specified outcomes, including barriers and facilitators to healthcare seeking for GDM after birth, were included. Two authors independently extracted data and assessed quality. Results were thematically synthesised. Results: Forty-two studies were included, with data from 7949 women in several countries. The diagnosis of GDM was sometimes a concerning or upsetting experience. A need for more specific information about GDM to be available around the time of diagnosis was identified. Women had varied experiences of antenatal GDM care and management, ranging from very positive to difficult and confusing. Non-judgemental and positively focussed care was preferred. While women were often knowledgeable about type 2 diabetes risk and prevention, they faced multiple barriers to undertaking preventive behaviours. A need for lifestyle change support and more pro-active postpartum care was identified. Conclusions: Provision of improved GDM education, as well as positive and pro-active care from diagnosis until postpartum follow-up may increase healthcare seeking by women with recent GDM.